Mysteries of TGF-β Paradox in Benign and Malignant Cells - Zhang, Qiang; Yu, Nengwang; Lee, Chung (Frontiers in Oncology, 2014)
TGF-β regulates a wide range of biological functions including embryonic development, wound healing, organogenesis, immune modulation, and cancer progression. Interestingly, TGF-β is known to inhibit cell growth in benign cells but promote progression in cancer cells, a phenomenon known as TGF-β paradox. To date, the mechanism of this paradox still remains as a scientific mystery. In this review, we present our experience, alone with the literature, in an attempt to offer answers to this mystery. First, we observed that, upon TGF-β engagement, there is a differential activation of Erk between benign and cancer cells. Since activated Erk is a major mediator in tumor progression and metastasis, a differentially activated Erk represents the answer to this mystery. Second, we identified a key player, PP2A-B56α, which is differentially recruited by the activated type I TGF-β receptor (TBRI) in benign and tumor cells, resulting in differential Erk activation. Finally, TGF-β stimulation leads to a suppressed TBRs in tumor cells but not in benign cells. This differentially suppressed TBRs triggers differential recruitment of PP2A-B56α and, thus, differential activation of Erk. The above three events offer the explanation to the mysteries